Skąd pochodzą polskie nazwy kolorów - Agnieszka Madeja (Postscriptum Polonistyczne)
The article attempts to explain the origin of some Polish names of non‑basic colours. Lexemes that serve as bases for forming the names of colours in Polish have been divided into four semantic categories. The most numerous one consists of the names of colours derivative from the names of certain plants. Second most numerous group of lexemes is based on the names of minerals, metals, stones. The third one refers to the names of animals, birds, fish and reptiles. The last, and least numerous group consists of the names of colours that originate from the names of the staining substances. Among the names of the colours presented in the article some examples can be found that do not belong to any of the four groups. The name of the colour can also originate from grocery articles, atmospheric phenomena, drinks or proper nouns.